Sociale gemengdheid in de openbare stedelijke ontwikkeling te Brussel: project of politiek taalgebruik? - Emmanuelle Lenel (Brussels Studies, 2013)
After regaining momentum in the mid 1990s, the principle of social mix crystallised at the beginning of the 2000s in a political approach to “reinforce social cohesion”. Since then, it has become a watchword for public urban action in Brussels and elsewhere in Europe. This article endeavours to give an outline of the political and ideological context in which it takes place, as well as attempting to show what is included in the social mix “project” in the case of Brussels – its intentions, instruments and matters left unsaid – and the urban challenges it reveals.